Enhancing High School Students' Critical Thinking Skills through STEM-PjBL in Optics Topic - Fanzuruni Fauhatun Mabrurah; Riskan Qadar; Nurul Fitriyah Sulaeman (Universitas Lambung Mangkurat, 2023)
Critical Thinking is one of the most crucial skills that must be trained and improved in learning. This study aims to improve students' critical thinking skills using Project-Based Learning (PjBL) model with a STEM approach (STEM-PjBL) on optics topics. This study used a quantitative approach and one group pretest-posttest design. The sampling technique used cluster random sampling and the sample used consisted of 35 students of a class in a public high school at Samarinda. Data collection uses test techniques with 6 questions in the form of essays. The results of this study showed that using STEM-PjBL on optics topics can significantly improve students' critical thinking skills with sig values. (2-tailed) in paired T-test 0.000 and N-Gain 0.74, which is included in the high criteria. After learning, 34% of students are in the highly critical category and 66% in the critical category. The PjBL model with the STEM approach can be used to train the critical thinking skills of high school students.